2017
DOI: 10.7717/peerj.3654
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of vitamin D3(cholecalciferol) in ulcerative colitis patients with hypovitaminosis D3

Abstract: AimTo prospectively evaluate the effects of vitamin D3 on disease activity and quality of life in ulcerative colitis (UC) patients with hypovitaminosis D.MethodsThe study was a prospective double-blinded, randomized trial conducted at Community Regional Medical Center, Fresno, CA from 2012–2013. Patients with UC and a serum 25(OH)D level <30 ng/ml were eligible for the study. Enrolled subjects were randomized to receive either 2,000 IU or 4,000 IU of oral vitamin D3 daily for a total of 90 days. The Short IBD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 18 publications
4
25
0
2
Order By: Relevance
“…However, in most cases, it was the small number of patients receiving corticosteroids that were being prescribed calcium and vitamin D supplements. Similar to our data, there are a few studies dem- onstrating that the prescription of oral vitamin D does not always improve the serum vitamin D levels in all patients and is dose dependent [4,26,27]. There is no evidence of improved disease activity in UC patients when given oral vitamin D supplements [4] unlike in CD patients were evidence exists of decreased disease activity and lower risk of relapse [28][29][30].…”
Section: Discussionsupporting
confidence: 74%
“…However, in most cases, it was the small number of patients receiving corticosteroids that were being prescribed calcium and vitamin D supplements. Similar to our data, there are a few studies dem- onstrating that the prescription of oral vitamin D does not always improve the serum vitamin D levels in all patients and is dose dependent [4,26,27]. There is no evidence of improved disease activity in UC patients when given oral vitamin D supplements [4] unlike in CD patients were evidence exists of decreased disease activity and lower risk of relapse [28][29][30].…”
Section: Discussionsupporting
confidence: 74%
“…68 A similar study in UC patients with serum vitamin D levels under 30ng/mL found that daily 4000 IU supplementation over 90 days improved patient quality of life but did not significantly improve clinical UC disease activity. 69 …”
Section: Vitamin D and Human Intestinal Inflammationmentioning
confidence: 99%
“…Hence, knowledge on the effects of 1,25(OH) 2 D treatment on the osteogenic function of M1 macrophages at fracture sites and on bone repair can shed light on the role of the 2 distinct macrophage subsets in bone repair. Additionally, knowing the effects of 1,25(OH) 2 D treatment on bone repair is particularly important because there is an increasing interest in the supplementation of vitamin D for the prevention and treatment of various human diseases (e.g., multiple sclerosis, inflammatory bowel disease, and diabetes) due to an association of vitamin D deficiency with these diseases (18)(19)(20)(21). More importantly, these diseases are frequently attended by an increasing risk of bone injuries (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%